2018
DOI: 10.1017/cjn.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Hospitalized Ischemic Stroke Patients with Dementia on Admission: A Population-Based Cohort Study

Abstract: During the observed period, 313,138 people were admitted to a hospital in Canada for an ischemic stroke. Of those, 21,788 (7.0%) had a concurrent diagnosis of dementia. People with dementia had older median age (84 vs. 76 years; p<0.0001), were more often female (59.6% vs. 48.4%; p<0.0001) and more often had Charlson-Deyo Comorbidity Index ≥2 (64.5% vs. 43.5%; p<0.0001). Patients with dementia were less likely to be discharged to a rehabilitation facility (adjusted risk ratio [RR] 3.089, 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The diagnostic codes used to identify hospitalizations for VCI included a range of codes which included vascular dementia, mild cognitive impairment, and Alzheimer disease-related diagnostic codes to capture dementia of possible or probable vascular contribution. 22,23 This is in line with recent coding standards 23 and with research supporting cognitive impairment and dementia as frequently a combination of Alzheimer pathology and microvascular damage. 24…”
Section: Data Sources and Study Populationsupporting
confidence: 75%
“…The diagnostic codes used to identify hospitalizations for VCI included a range of codes which included vascular dementia, mild cognitive impairment, and Alzheimer disease-related diagnostic codes to capture dementia of possible or probable vascular contribution. 22,23 This is in line with recent coding standards 23 and with research supporting cognitive impairment and dementia as frequently a combination of Alzheimer pathology and microvascular damage. 24…”
Section: Data Sources and Study Populationsupporting
confidence: 75%
“…7,25,35 Throughout the sources reviewed, patients with a higher mRS were typically older, had more comorbidities, had had more severe strokes, had had previous strokes, had diabetes mellitus, experienced atrial fibrillation, and were more likely to catch pneumonia. 16,22,33…”
Section: Resultsmentioning
confidence: 99%
“…7,25,35 Throughout the sources reviewed, patients with a higher mRS were typically older, had more comorbidities, had had more severe strokes, had had previous strokes, had diabetes mellitus, experienced atrial fibrillation, and were more likely to catch pneumonia. 16,22,33 Busl et al 16 found that patients ≥80 with AIS treated with IVT had a decreased likelihood of death, illustrating that age as a single variable does not limit the benefit of intervention for individuals. The finding of age not predicting stroke outcome was replicated by Murao et al, 35 who additionally found that cognitive impairment, no dementia (CIND), and onset to needle time were not associated with a positive outcome.…”
Section: Multinationalmentioning
confidence: 99%
“…While the evolution of healthcare has contributed to increasing the population's life expectancy, the number of individuals living with noncommunicable diseases such as dementia is on the rise. In 2015, the World Health Organization reported 47.5 million people living with dementia (PLWD) and postulated that this will increase to 75.6 million by 2030 [1]. Challenges that PLWD encounter include memory loss, depression, anxiety, isolation, inability to live independently, and loss of a sense of self [2].…”
Section: Introductionmentioning
confidence: 99%